Use of BD BACTEC™ MGIT™ for the detection of non-tuberculous mycobacteria in sanitary water samples - Ferraro, Vincenzo; Bisognin, Francesco; Sorella, Federica; Ruin, Federica; Dal Monte, Paola (Frontiers in Microbiology, 2024)
The most commonly used method for the detection of nontuberculous mycobacteria (NTM) is culture in BD BACTEC™ MGIT™ Mycobacteria Growth Indicator Tubes incubated in an automated growth detection reader BD BACTEC™ MGIT™ 960 Instrument. The system is currently validated for the detection of mycobacteria from clinical specimens but not environmental matrices. From November 2018 to December 2023, 1369 sanitary water samples from 92 Heater Cooler Units (HCU) and 747 sanitary water samples from 489 Haemodialysis instruments (Dialysis) were concentrated, decontaminated, and cultured on MGIT and solid Lowenstein-Jensen media to evaluate the presence of NTM. NTM positive cultures (n = 261 HCUs and n= 20 dialysis) were purified by Middlebrook 7H11 agar plate subcultures and identify by MALDI-TOF mass spectrometry technology . The purpose of this study is to evaluate the accuracy and reproducibility of the MGIT system on sanitary water from HCU and Dialysis, using as sources of NTM the two strains most frequently isolated on these devices during Emilia-Romagna surveillance programme: M. chimaera (79%) and M. saskatchewanense (100%), respectively. To evaluate accuracy, sanitary water were spiked with M. chimaera and M. saskatchewanense at the theoretical concentration of 100 and 10 CFU/ml, and all resulted positive in MGIT tube. No significant changes in Time to Positivity were observed when MGIT tubes was inoculated with NTM at the theoretical concentration of 10 and 100 CFU/ml on 3 consecutive days, indicating that detection method is reproducible. The MGIT system is suitable to detect the presence of NTM in sanitary water samples, as it was capable of detecting up to 4 CFU/ml for both M. chimaera and M. saskatchewanense. Our results indicate that MGIT system can be used for NTM detection not only for clinical samples, but also environmental matrices.